Frontal lobe and long-term memory retrieval analysis during pre-learning stress using EEG signals - Omar Mahmoud AlShorman; Ahmad M. Alshorman (Institute of Advanced Engineering and Science, 2020)
This paper uses the EEG analysis to investigate the relationship between pre-learning stress, frontal lope and long-term memory in the brain. The stress on learning stage is a challenge, especially in academic life. Stress also on learning stage affects the retrieval or recall from the memory. Nowadays; there are many recent works have discovered the relationship between stress, learning and memory performance based on different techniques. Some of these techniques are biological methods. Moreover, these methods have discovered the effect of stress based on hormones levels such as cortisol, or based on physiological effects such as blood pressure. However, these techniques have given conflicting discoveries because of the instability of hormones and an extensive number of related elements. The main aim of this research is to discover the relationship between Pre-learning stress, frontal lope, and long-term memory retrieval using EEG signals. The experimental results indicate that there is a relationship between theta rhythm in the frontal lobe and long-term memory retrieval during Pre-learning stress.